2016
DOI: 10.1093/ehjcvp/pvw005
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 receptor inhibitors in patients with non-ST-elevation acute coronary syndrome in the real world: use, patient selection, and outcomes from contemporary European registries

Abstract: There were substantial differences in the use of and patient selection for clopidogrel, prasugrel, and ticagrelor, which were associated with differences in short- and long-term ischaemic and bleeding events. In future registries, data collection should be performed in a more standardized way with respect to endpoints, definitions, and time points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 11 publications
1
21
0
5
Order By: Relevance
“…Although some real-world analyses have shown an association with higher bleeding risk, 29 this observation is not consistent in all registries. [30][31][32] Indeed, the last data coming from Spain showed no differences after matching-cohort analysis. 22 In the light of these results, it might be suggested that there is no such increase in bleeding risk when third-generation P2Y 12 inhibitors are used, particularly in CKD patients.…”
Section: Discussionmentioning
confidence: 94%
“…Although some real-world analyses have shown an association with higher bleeding risk, 29 this observation is not consistent in all registries. [30][31][32] Indeed, the last data coming from Spain showed no differences after matching-cohort analysis. 22 In the light of these results, it might be suggested that there is no such increase in bleeding risk when third-generation P2Y 12 inhibitors are used, particularly in CKD patients.…”
Section: Discussionmentioning
confidence: 94%
“…1), и блокаторы (ингибиторы) P2Y 12 аде-нозиновых рецепторов тромбоцитов (клопидогрел, прасугрел, тикагрелор) [3,4]. Наиболее часто приме-няемыми в настоящее время ААП являются АСК и клопидогрел (рис.…”
Section: основные антитромбоцитарные средстваunclassified
“…В реальной клинической практике частота летальных исходов, ишемических событий, а также частота кровотечений были такими же или даже превышали данные, полученные в ходе ран-домизированных клинических исследований блокаторов P2Y 12 рецепторов. Эти различия объясняются прин-ципами отбора пациентов в рандомизированные кли-нические исследования [4].…”
Section: основные антитромбоцитарные средстваunclassified
See 1 more Smart Citation
“…Depending on the clinical setting, the duration of DAPT may range from one month to more than one year [5,6]. Data from major trials and registries have shown that approximately 9%-10% of patients receiving DAPT experienced a thrombotic event within one year, whereas bleeding events occurred in about 2% of patients [3,7,8]. This suggests that individualized antiplatelet regimens, tailoring both DAPT potency as well as duration, might be beneficial in terms of net clinical benefit (i.e., the combination of ischemic and bleeding events).…”
Section: Introductionmentioning
confidence: 99%